1999
DOI: 10.1021/ic990003g
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Based Redox Isomers of [ZnII(C28H40NO2)2]:  Molecular and Electronic Structures of a Diamagnetic Green and a Paramagnetic Red Form

Abstract: The tridentate trianion of N,N-bis(2-hydroxy-di-3,5-tert-butylphenyl)amine, H(3)L(3), forms 1:1 and 2:1 complexes with di-, tri-, or tetravalent transition metal ions where it can exist in four oxidation levels (C(28)H(40)NO(2))(3)(-)(,2)(-)(,1)(-)(,0), which are herein designated as L(3), L(2), L(1), and L(0), respectively; (L(2))(2)(-) and (L(0))(0) are paramagnetic (S = (1)/(2)), whereas the other two are diamagnetic (S = 0). We have synthesized the complexes [Zn(L(2))(NEt(3))] (1), green [Zn(L(1))(2)] (2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 15 publications
8
61
0
3
Order By: Relevance
“…[18] Deprotonation of (ON-O cat )H 3 with 3 equiv. nBuLi affords the trianionic form of the ligand, (ONO cat ) 3-.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Deprotonation of (ON-O cat )H 3 with 3 equiv. nBuLi affords the trianionic form of the ligand, (ONO cat ) 3-.…”
Section: Resultsmentioning
confidence: 99%
“…[21] The tridentate Schiff-base ligand 3,5-ditert-butyl-1,2-quinone-1-(2-hydroxy-3,5-di-tert-butylphenyl)-A C H T U N G T R E N N U N G imine [22] leads to stable coordination complexes with several metal ions, and exhibit different oxidation states ranging from 0 to À3 (see Scheme 1). Nevertheless, it usually coordinates in the mononegative Cat-N-BQ À or dinegative Cat-N-SQ 2À radical forms [23] generating mixed-valence species. Although complexes 2-4 have been previously synthesized, only preliminary studies on the IET LM of complex 2 have been reported.…”
Section: Ma C H T U N G T R E N N U N G (Cat-n-bq)a C H T U N G T R Ementioning
confidence: 99%
“…For instance, the tridentate ligand [(2-hydroxy-3,5-di-tert-butyl-1-phenyl)imino]-3,5-di-tert-butyl-1,2-benzoquinone ligand (Cat-N-BQ), may in principle exist in different oxidation states although it usually coordinates in the mononegative Cat-N-BQ or dinegative Cat-N-SQ radical forms (see Scheme 4). [63] Using such a ligand, in 1988 Pierpont et al reported the new complex [Co III (Cat-N-BQ)(Cat-N-SQ)] (12), although at that time no evidence for tautomeric interconversion was shown to take place. [64] A few years later, the temperature dependence of the spectral and magnetic properties of solutions of this compound in nonpolar solvents suggested the existence of the valence tautomeric equilibrium shown in Equation (4).…”
Section: Phenoxyl Ligandsmentioning
confidence: 99%